SHM_415274_HST_3D Lihult Stone Axe - Qallaki, Ylber; Lernestål, Erik; Strandberg, Caroline; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a Mesolithic stone axe collected from Lihult in Västra Götaland in 1883, currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=691

Link to Sök I Samlingarna

https://samlingar.shm.se/object/D61924F2-EAC3-441C-A7F1-32951D1CEF93
Keywords: 3D Model; Museum Object; Archaeology; Archaeology; Photogrammetry; History and archaeology; Archaeology/history; Dynamic Collections; Swedish Mesolithic; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi